2020
DOI: 10.3390/jcm9113523
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Neurovascular Coupling on Optical Coherence Tomography Angiography Is the Earliest Detectable Abnormality before Clinical Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) has traditionally been viewed as either a microvasculopathy or a neuropathy, though neurovascular coupling deficits have also been reported and could potentially be the earliest derangement in DR. To better understand neurovascular coupling in the diabetic retina, we investigated retinal hemodynamics by optical coherence tomography angiography (OCTA) in individuals with diabetes mellitus (DM) but without DR (DM no DR) and mild non-proliferative DR (mild NPDR) compared to healthy eyes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…An early increase in retinal blood flow in the SCP in DM with no DR, as observed in this study, has been already reported in recent studies 5–7 and interpreted as a compensatory effect to initial capillary occlusion, maybe due to regulatory mechanisms separate from those of deeper vessels and capable of preserving flow at this level. 6 Similarly, Ashraf et al 27 found no correlation between changes observed in the SCP and in the DCP in different DR stages, thus suggesting that these changes may be at least partially independent.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…An early increase in retinal blood flow in the SCP in DM with no DR, as observed in this study, has been already reported in recent studies 5–7 and interpreted as a compensatory effect to initial capillary occlusion, maybe due to regulatory mechanisms separate from those of deeper vessels and capable of preserving flow at this level. 6 Similarly, Ashraf et al 27 found no correlation between changes observed in the SCP and in the DCP in different DR stages, thus suggesting that these changes may be at least partially independent.…”
Section: Discussionsupporting
confidence: 88%
“…D iabetic retinopathy (DR) was recently defined as a "highly tissue-specific neurovascular complication" of both Type 1 and Type 2 diabetes mellitus (DM1/DM2) 1 and subclinical evidence of both neuronal and microvascular damage before clinically evident DR has been widely reported. [2][3][4][5][6][7] Even if diabetes mellitus (DM), and especially DM2, prevalence is increasing, 8 most evidence indicates that patients with DM can significantly reduce the risk of diabetes-related complications by maintaining an optimal long-term metabolic control with low glycated hemoglobin (HbA1c) variability. [9][10][11] Current recommendations indicate a target HbA1c level # 6.5% in DM1 and #7% in DM2 to minimize the risk of long-term vascular complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15] Diabetes-induced changes in the ERG may be attributed to neuronal dysfunction, 7,11,16,17 changes in the levels of neurotransmitters, [17][18][19][20] and cell death in the neural retina. 18 In addition, early vascular changes, such as increased vascular permeability as early as 1 week after hyperglycemia in diabetic rodents, 21,22 or structural vascular abnormalities detected with optical coherence tomography angiography in patients with diabetes and no visible microvascular fundus changes [23][24][25] may alter neuronal function owing to neurovascular coupling.…”
Section: Introductionmentioning
confidence: 99%
“…As Figure 3A-3F shows, compared with normal eyes, mild NPDR eyes had a small amount of non-perfusion and microvascular tumors in the wide-field OCTA (WF-OCTA) images ( 44 ). As DR progresses from moderate to severe NPDR, the number of non-perfusion areas and microaneurysms increases, and blood vessels become distorted and dilated ( 45 ) ( Figure 3G-3I ).…”
Section: Resultsmentioning
confidence: 99%